Software client for first-person-shooting (FPS) games - Zhou, Weicheng. (2009)
First Person Shooting (FPS) games are popular among internet users with rapid growth trend. However players have difficulties in finding game servers to play as well as socializing with others. This project focuses primarily on solving the issue of finding game servers by providing a software client with server search function. This report contains an introduction to explain the issue, followed by a review of existing solutions. Online survey is conducted to understand the needs of the gamers. Features of the software client are decided according to the survey result. The report also includes a complete project technical development cycle from initial designs to project deployment. Various user behaviors are analyzed based on the data gathered from December 2008 to March 2009. In the end, an overall review of the project is provided and further recommendations are given.